1991
DOI: 10.1007/bf01958435
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin alfa in anaemic children or adolescents on regular dialysis

Abstract: Eighteen patients aged 5-18 years on regular dialysis had a packed cell volume (PCV) less than 0.27. On treatment with epoetin alfa (EA) PCV increased by 0.05 or more in all patients. Iron supplementation was necessary in 13 patients with a ferritinaemia less than 300 micrograms/l before study. During treatment, plasma potassium increased significantly and more vigorous antihypertensive measures were required in 8 patients, 5 of them being already on antihypertensive drugs before EA. Iliofemoral thrombosis occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Serum ferritin levels fell independently of the dose of rHuEPO but somewhat faster than is normally observed in early postnatal life [16]. These changes constitute additional evidence that rHuEPO effectively stimulated the proliferaton of the erythroid cell pool, thereby increasing the incorporation of circulating iron into maturing red cells, as shown in older patients [3,10,28]. Interestingly, the standard dose of oral iron (2-5 mg/kg per day) that is usually sufficient to prevent late iron deficiency anaemia in premature infants proved insufficient in some patients to sustain effective erythropoiesis during rHuEPO therapy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Serum ferritin levels fell independently of the dose of rHuEPO but somewhat faster than is normally observed in early postnatal life [16]. These changes constitute additional evidence that rHuEPO effectively stimulated the proliferaton of the erythroid cell pool, thereby increasing the incorporation of circulating iron into maturing red cells, as shown in older patients [3,10,28]. Interestingly, the standard dose of oral iron (2-5 mg/kg per day) that is usually sufficient to prevent late iron deficiency anaemia in premature infants proved insufficient in some patients to sustain effective erythropoiesis during rHuEPO therapy.…”
Section: Discussionmentioning
confidence: 85%
“…No or minimal platelet count changes have been observed in adults [10,28] or in children [3] treated with rHuEPO, but thrombocytosis has been described in murine studies [2] during the first days of therapy. An effect of rHuEPO on megakaryocytopoiesis has been postulated [11], but thrombocytosis is commonly associated with iron depletion [23], and could have resulted in our patients from the rapid fall in serum iron concentration that occurred during rHuEPO therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Controlled trials in children support rHuEPO use in both hemodialysis and peritoneal dialysis. Lerner et al demonstrated that rHuEPO use is common: 81% of patients were administered erythropoietin at baseline and 93% of patients after two years of dialysis.…”
Section: Renal Failurementioning
confidence: 99%
“…Exacerbation of hypertension has been reported by several authors in both non-dialysis CKD and children on dialysis [14][15][16][17][18][19]. However, many of the studies excluded children with moderate or uncontrolled hypertension, either before or during the trial period.…”
mentioning
confidence: 99%
“…Consequently, the use of lower doses of epoetin (approximately 150 U/kg per week) is recommended. In light of studies supporting a prothrombotic potential of epoetin in children, it has been suggested that epoetin administration be deferred for at least 2 weeks after surgery for arteriovenous (AV) fistula to prevent fistula thrombosis [13,14,21].…”
mentioning
confidence: 99%